Monitored Extended Secondary Arterial Ischemia in a Free Muscle Transfer - Sværdborg, Mille; Birke-Sørensen, Hanne (Journal of Reconstructive Microsurgery, 2012)
In reconstructive microsurgery, flap failure can be catastrophic to the patient. Different monitoring methods have been implemented in an attempt to recognize secondary ischemia during its early stages. However, the exact onset of secondary ischemia can be difficult to determine because there are no well-documented and reliable monitoring techniques that offer true continuous monitoring in a clinical setting. Because of the uncertain time in terms of the onset of secondary ischemia, the exact length of ischemia before revascularization, the secondary ischemia time, cannot be obtained. This is probably part of the reason why not much has been published regarding the effect of secondary ischemia time in reference to flap survival. We present a case of a free gracilis muscle flap that was salvaged despite more than 11 hours of arterial ischemia. The flap was monitored using microdialysis and at no time was the ischemia clearly demonstrated by clinical inspection. We conclude that clinical monitoring in some cases can be an unreliable method for monitoring free muscle transfers suffering from arterial ischemia and that further studies are needed for more specific guidelines regarding the critical secondary ischemia time in muscle flaps.
Keywords: microsurgery; monitoring; microdialysis; muscle; ischemia